2019
DOI: 10.3389/fpsyg.2019.00796
|View full text |Cite
|
Sign up to set email alerts
|

12 Weeks of Kindergarten-Based Yoga Practice Increases Visual Attention, Visual-Motor Precision and Decreases Behavior of Inattention and Hyperactivity in 5-Year-Old Children

Abstract: The present study assesses the impact of Kindergarten-based yoga on cognitive performance, visual-motor coordination, and behavior of inattention and hyperactivity in 5-year-old children. In this randomized controlled trial, 45 children (28 female; 17 male; 5.2 ± 0.4 years) participated. Over 12 weeks, 15 children performed Hatha-yoga twice a week for 30 min, another 15 children performed generic physical education (PE) twice a week for 30 min, and 15 children performed no kind of physical activities, serving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 70 publications
2
51
0
6
Order By: Relevance
“…Only one study, incorporated all cognitive aspects of self-regulation and found that there were improvements in attention, working memory, and inhibition, as result of the PA intervention [22]. In the current review, attention was the only component of self-regulation that consistently showed improvement as a result of the PA interventions [19][20][21][22]. The findings for working memory and inhibition were inconclusive regarding changes in these variables with PA. Half of the studies (1 of 2) showed a positive impact of PA on working memory, and three of five studies found a positive impact of PA on inhibition [20,22,24].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Only one study, incorporated all cognitive aspects of self-regulation and found that there were improvements in attention, working memory, and inhibition, as result of the PA intervention [22]. In the current review, attention was the only component of self-regulation that consistently showed improvement as a result of the PA interventions [19][20][21][22]. The findings for working memory and inhibition were inconclusive regarding changes in these variables with PA. Half of the studies (1 of 2) showed a positive impact of PA on working memory, and three of five studies found a positive impact of PA on inhibition [20,22,24].…”
Section: Discussionmentioning
confidence: 61%
“…After corrections, the only significant interaction effect that remained was that yoga had an impact on the precision of detection in comparison to the control group (adj. p = 0.005; ηp 2 = 0.164) [19]. The effect size was considered large and these findings demonstrated a positive impact of yoga on attention control.…”
Section: Attentionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, several studies reported that the practice of physical activity (PA) improves FMS level by inducing a higher MC in childhood (Fisher et al, 2005;Hardy et al, 2010;Battaglia et al, 2018;Aivazidis et al, 2019;Nilsen et al, 2020a). For these reasons, the practice of structured PA in kindergarten during this period results to be crucial (Deli et al, 2006;Barbosa et al, 2016;Figueroa and An, 2017;Kippe and Lagestad, 2018;Alves and Alves, 2019;Jarraya et al, 2019). However, PA in preschool age is limited and, furthermore, the level of PA among children living in Europe varied considerably among countries (Konstabel et al, 2014).…”
Section: Introduction Motor Skillsmentioning
confidence: 99%